AKAR TERORISME DALAM ISLAM? - Sukendar, Sukendar (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2012)
Terrorism has been a popular issue since September the Eleven. The incident was followed by a proclamation of war against terrorism by the US governments. The US invited other countries to join the campaign with President George W. Bush's monumental saying